Genetic polymorphism in matrix metalloproteinase‐9 and transforming growth factor‐β1 and susceptibility to combined pulmonary fibrosis and emphysema in a Chinese population. Issue 3 (19th January 2017) - Xu, Ling; Bian, Wei; Gu, Xiao‐Hua; Shen, Ce
Abstract: In this study, we aimed to explore the association of genetic polymorphism in matrix metalloproteinase‐9 ( MMP‐9 ) and transforming growth factor‐β1 ( TGF‐β1 ) and the susceptibility to combined pulmonary fibrosis and emphysema (CPFE). We examined the polymorphisms of the MMP‐9 C‐1562T and TGF‐β1 T869C in 38 CPFE patients, 50 pulmonary emphysema patients, and 34 idiopathic pulmonary fibrosis (IPF) patients. The frequencies of polymorphic genotypes in MMP‐9 were 78.95% CC and 21.05% CT in CPFE group, 76.0% CC and 24.0% CT in emphysema group, and 100.0% CC in IPF group. There were highly statistically significant increased frequencies of the CT genotype and T allele in CPFE and emphysema groups compared with IPF group ( p < 0.05). The frequencies of polymorphic genotypes in TGF‐β1 were 2.63% CC, 28.95% CT, 68.42% TT in CPFE group, 4.00% CC, 16.00% CT, 80.00% TT in emphysema group, and 5.88% CC, 41.18% CT, 52.94% TT in IPF group. Significant increases in the TT genotype and T allele frequencies were observed in emphysema group compared with IPF group ( p < 0.05). Our study has showed that T allele in MMP‐9 (C‐1562T) and T allele in TGF‐β1 (T869C) are risk factors of pulmonary emphysema. The T allele in MMP‐9 (C‐1562T) possibly predisposes patients with pulmonary fibrosis to develop emphysema.